Chorioamniotic membrane separation following fetal myelomeningocele repair: incidence, risk factors and impact on perinatal outcome. (2nd November 2020) - Corroenne, R.; Yepez, M.; Barth, J.; Pan, E.; Whitehead, W. E.; Espinoza, J.; Shamshirsaz, A. A.; Nassr, A. A.; Belfort, M. A.; Sanz Cortes, M.
ABSTRACT: Objectives: Prenatal myelomeningocele (MMC) repair has been shown to provide significant benefits to the infant, decreasing the postnatal need for ventriculoperitoneal shunt and improving motor outcome. Chorioamniotic membrane separation (CAS) is a potential complication following prenatal MMC repair and may increase the risk of preterm prelabor rupture of membranes (PPROM) and preterm birth. The objectives of this study were: (1) to evaluate the incidence of CAS after prenatal MMC repair; (2) to determine risk factors associated with its occurrence; and (3) to assess its association with adverse perinatal outcomes. Methods: This was a retrospective cohort study of patients who underwent fetal MMC repair between November 2011 and December 2018. Surgery was performed using either a fetoscopic (laparotomy or exteriorized uterus) approach or an open‐hysterotomy approach. Eligibility criteria were those reported in the Management of Myelomeningocele Study. If CAS was detected on ultrasound (US), its severity was graded as 'mild' if amnion detachment involved < 25% of the uterine cavity, 'moderate' if it involved 25–50% and 'severe' if it involved > 50%. Evolution of CAS was classified as stable, increasing or decreasing based on the difference in severity grading between the time at first diagnosis and the last US scan before delivery. Logistic regression analysis was performed to identify pre‐ or perisurgical factors associated with the development of CAS and to determine the risk of adverse perinatal outcome associated with CAS. Results: In total, 91 cases were included. Fetoscopic or open‐hysterotomy repair of MMC was performed in 52/91 (57.1%) and 39/91 (42.9%) cases, at a median gestational age (GA) of 25.0 weeks (range, 22.9–26.0 weeks) and 25.0 weeks (range, 21.3–25.9 weeks), respectively. CAS was diagnosed in 31/91 (34.1%) patients, at a median GA of 28.1 weeks (range, 24.4–37.6 weeks). Anterior placenta was identified as a risk factor for the postoperative development of CAS (odds ratio (OR), 3.72 (95% CI, 1.46–9.5); P < 0.01). This risk was dependent on the repair technique. An anterior placenta significantly increased the risk of CAS after fetoscopic repair (OR, 3.94 (95% CI, 1.14–13.6); P = 0.03) but not after open repair (OR, 2.8 (95% CI, 0.6–12.5); P = 0.16). There was no significant difference in the rate of CAS after fetoscopic repair (21/52 (40.4%)) vs open‐hysterotomy repair (10/39 (25.6%)) ( P = 0.14), nor were there any differences in GA at diagnosis of CAS, interval between surgery and diagnosis, distribution of CAS severity or progression of CAS between the two groups. CAS increased the risk of PPROM (50% in those with vs 12% in those without CAS) (OR, 7.6 (95% CI, 2.5–21.9); P < 0.01) and preterm delivery (70% vs 38%) (OR, 3.2 (95% CI, 1.3–8.1); P < 0.01). Fetoscopically repaired cases with CAS had a higher rate of PPROM (12/20 (60.0%) vs 2/31 (6.5%); P < 0.01) and preterm delivery (13/20 (65.0%) vs 5/31 (16.1%); P < 0.01) than those that did not develop CAS, while the differences were not significant in cases with open‐hysterotomy repair. Early detection of CAS (before 30 weeks' gestation) was a risk factor for preterm delivery (90% before 30 weeks vs 36% at or after 30 weeks) (OR, 15.7 (95% CI, 2.3–106.3); P < 0.01). There was no association between PPROM or preterm delivery and the severity or progression of CAS. Conclusions: The presence of an anterior placenta was the only factor that increased the risk for CAS after fetoscopic MMC repair. Detection of CAS after fetoscopic MMC repair significantly increases the risk for PPROM and preterm delivery. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.